(3OjhGf GHf eWQhMs - (3jMji Hf YjSi Hf EHQGgje GdeUQj , LeGd GdOjf, GHf eWQhM,J (B649 (3g` s
(3ChdgG (B:s
(3bGd GdUGMH LeGd GdOjf GHf eWQhM gi QGeI aNP hCjejf GdhGOi hPQ GdSjha JbQ ai GdCZeGO s
(3BNQgG (B:s
(3Je GdOjhGf GdeHGQc HMeO Gddg hYhfg hMSf Jhajbgq s
(3GdfSNI HgG MhGTs
(3HOGNd GdOjhGf TYQ dZjQ GdTGYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B109s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B768s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs